The unfolded protein response in virus infections - Shiu-Wan Chan (Frontiers Research Topics, 2015)
Unfolded protein response (UPR) is a cellular adaptive response for restoring endoplasmic reticulum (ER) homeostasis in response to ER stress. Perturbation of the UPR and failure to restore ER homeostasis inevitably leads to diseases. It has now become evident that perturbation of the UPR is the cause of many important human diseases such as neurodegenerative diseases, cystic fibrosis, diabetes and cancer. It has recently emerged that virus infections can trigger the UPR but the relationship between virus infections and host UPR is intriguing. On one hand, UPR is harmful to the virus and virus has developed means to subvert the UPR. On the other hand, virus exploits the host UPR to assist in its own infection, gene expression, establishment of persistence, reactivation from latency and to evade the immune response. When this delicate balance of virus-host UPR interaction is broken down, it may cause diseases. This is particularly challenging for viruses that establish a chronic infection to maintain this balance. Each virus interacts with the host UPR in a different way to suit their life style and how the virus interacts with the host UPR can define the characteristic of a particular virus infection. Understanding how a particular virus interacts with the host UPR may pave the way to the design of a new class of anti-viral that targets this particular pathway to skew the response towards anti-virus. This knowledge can also be translated into the clinics to help re-design oncolytic virotherapy and gene therapy. In this research topic we aimed to compile a collection of focused review articles, original research articles, commentary, opinion, hypothesis and methods to highlight the current advances in this burgeoning area of research, in an attempt to provide an in-depth understanding of how viruses interact with the host UPR, which may be beneficial to the future combat of viral and human diseases.